BANKING SECTOR IN PAKISTAN AND CREDIT RISK: EMPIRICAL STUDY ON DETERMINANTS OF CREDIT RISK AND THEIR EVOLUTION IN PAKISTAN’S CONVENTIONAL AND ISLAMIC BANKS - Jamil, Wahaj (2011)
Banking sector in Pakistan has witnessed tremendous growth in the last decade, owing to the financial reforms in the 1990’s which attempted to liberalise the sector. Furthermore Pakistani banks also recently witnessed the consequences of the global financial crisis which has amplified the non-performing loans (NPLs) within the sector. This enhanced the management’s interest of various commercial banks and the governing central bank, State Bank of Pakistan, in risk management procedures and more specifically credit risk. To address these credit risk problems, an effort is made to determine what really influences credit risk in Pakistani banks. Additionally with the inclusion of Islamic banks in Pakistan from 2002 made this research more appealing as comparison on credit risk can be made keeping in view these two diverging banking systems. Theoretically Islamic banks are considerably different in their operations; hence there should be differences in Islamic and conventional banks in every aspect, including credit risk. These views are considered guided by an extensive literature to build and analyse three hypotheses (i) determinants of credit risk in Pakistani banking sector, (ii) differences in credit risk between Islamic and conventional banks and (iii) 2007’s financial crisis impact on Pakistani banks. These hypotheses are analysed using a panel-data regression for 23 banks currently operating in Pakistan, out of which 5 are Islamic banks, considering for five accounting periods from 2006 to 2010. The results generated are presented with their detailed logical inferences investigating an underdeveloped economy for which evidence concerning credit risk determinants and its differences with regards to Islamic bank is non-existent, providing with a valuable conclusion and prospects for further research.